Mineralogy of a carbonatite - related fenite in Lower Swat, Northern Pakistan - Jan, M. Qasim; Ahmad, Irshad; Dipietro, Joseph A. (Journal of Himalayan Earth Sciences, 1999)
The Precambrian-Cambrian Manglaur formation contains several small bodies of carbonatite and fenite to the SE of Mingora. Their composition and close association with late Paleozoic granitic rocks is similar to these of the Naranji Kandao area in Buner. The entire suite may be related to Late Paleozoic rifting. The carbonatite is sugary sovite comprising calcite and clinopyroxene, with minor amounts of primary (?) clinozoisite, cancrinite- vishevite, apatite, sphene, opaques and zircon. The fenite consists of pure albite (abundant) calcite, biotite with > 3% MgO and minor magnetite.